(untitled) (Journal of the College of Basic Education, 2023)
Through the above research, it is clear to us that the rural housing units in the study region are apparently on their way to extinction, and the reason for this is due to the change in the mentality of the Kurdish farmer in the region itself, in addition to the extent of the change in the economic situation taking place in the standard of living, whether that is On the economic level of the urban population in the first place or in relation to the rural population, and it is known that the rural population are mostly imitators of others, so we find that the rural houses are also changing, without taking into consideration the climatic or terrain factors that exist in the region, and accordingly we find that the maps that were drawn up Building in the city of Aqrah is the same as that used in the countryside of the district, and therefore the farmer here has dispensed with a lot of rural spaces that were used previously, as is the case, for example, in placing facilities outside the rural housing unit or minimizing the animal enclosure instead of dispensing with it completely, just as the materials The product is available in the local markets at reasonable prices, in addition to other aspects such as wood that was used in the field of heating or used as fuel in the field of cooking, meaning that there is no compatibility Between the past and the present in the field of construction, but there is a process of replacing one map with another. The currency of exchange is easy and does not need much thinking to find a kind of compatibility between the past and the present. For example, until now, no one thinks about combining what is currently used in the field of energy consumption, so we do not find today Until now, those who think of an energy alternative as an alternative to oil or gas, as is the case with developed countries that seek to compensate for oil with inexhaustible solar energy, knowing that the summer of the region is long, so there is not a single solar energy project in it, that the gap is wide between the past The inherited and the present, and the person can look at the extent of construction between the two parties, which is currently diminishing and lacking, and the engineer or the person who puts the map for the rural housing unit must take into account everything in addition to the modern changes, and mix between the old and the new without neglecting or leaving any old side as Not suitable for the modern era.